A Decision Support System Using a Simple Additive Weighting Method to Make the Production Division of PT. Indofood Fortuna Makmur's Employee Selection Process More Simple - M. Subchan; Partono Siswosuharjo; Rizky Yulia (Universitas Ibn Khaldun Bogor, 2025)
At PT Indofood Fortuna Makmur, the information system still runs manually, especially when it comes to the program for choosing exceptional staff. Results of the examination are less precise and effective. The system must be developed by switching to a computer-based information system in order to prevent errors. With a calculation utilizing the SAW technique, an application that uses the PHP programming language and a MySQL database are used to design and build a decision-support system for choosing exceptional personnel. This application is in accordance with the issues at PT. Indofood Fortuna Makmur; the results are accurate because they are based on field assessments rather than biased assessments, and as a result of this assessment, employees at PT. Indofood Fortuna Makmur will be motivated to compete to become model workers.